(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
An environmental-friendly electroless copper plating process was employed in preparing copper-coated polyester fabric with excellent conductivity. The effects of bath temperature on the plating rate, compositions and crystal structure of the electroless copper deposits were studied. The results showed the deposition rate increased with the rise of the bath temperature. X-ray Diffraction (XRD) scan indicated that the copper coating deposited was well crystallized and Scanning Electron Microscopy (SEM) scan showed copper coating had good surface morphology. Surface resistance of copper plated polyester fabric was evaluated. The surface resistance was 16.5 m03a9/sq as the temperatue was 65 00a000baC.